Miejsce e-learningu w zarządzaniu wiedzą - Skrzypek, Elżbieta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
W artykule przedstawiono istotę i miejsce e-learningu w organizacji, pokazano obszary e-learningu, omówiono jego formy, wskazano wady i zalety zdalnego nauczania, porównano szkolenia tradycyjne i elektroniczne. Wskazano miejsce e-learningu w procesie zarządzania wiedzą. Celem artykułu jest wskazanie rosnącej roli rozwiązań e-learningowych we współczesnych organizacjach. Przeprowadzone w artykule analizy mają charakter teoretyczny i bazują na dorobku literatury naukowej.

The article discusses the nature and role of e-learning in the organization, presenting the areas of e-learning, its forms, the advantages and disadvantages of distance learning, traditional vs electronic education, the place of e-learning in the process of knowledge management in organizations. The purpose of this article to highlight the growing role of e-learning in contemporary organizations. Analysis carried out in the article is theoretical in nature and is based on the achievements of the scientific publications.
Keywords: e-learning; wiedza; zarządzanie wiedzą; rynek IT; technologie informacyjne; knowledge; knowledge management; IT market; information technology